2004
DOI: 10.1002/jmor.10280
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation dynamics and morphological differentiation during regeneration in Dorvillea bermudensis (Polychaeta, Dorvilleidae)

Abstract: Although some species of Annelida have an enormous capacity to regenerate, it is not yet known whether reestablishment of lost body parts is performed by stem cells, depends on preceding dedifferentiation of somatic cells, or is a combination of both. In order to clarify how, in the case of epimorphic regeneration, the blastemas are formed, we applied the thymidine analog 5'-bromo-2'-deoxyuridine (BrdU) in the dorvilleid polychaete Dorvillea bermudensis to identify cells in the S-phase of the cell cycle. Regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…Besides contraction of the musculature at the level of the wound, already 1 hour p-a, the wound was almost completely covered by a thin layer of flattened epidermal cells. The same mechanism was observed earlier for tail plate regeneration in M. lignano (Salvenmoser et al 2001;Nimeth et al 2007;Egger et al 2009) and regeneration in triclads, so-called planarians (Baguñà et al 1994;Sánchez Alvarado and Newmark 1998) and polychaetes (Paulus and Muller 2006).…”
Section: Wound Healing and Blastema Formationsupporting
confidence: 62%
“…Besides contraction of the musculature at the level of the wound, already 1 hour p-a, the wound was almost completely covered by a thin layer of flattened epidermal cells. The same mechanism was observed earlier for tail plate regeneration in M. lignano (Salvenmoser et al 2001;Nimeth et al 2007;Egger et al 2009) and regeneration in triclads, so-called planarians (Baguñà et al 1994;Sánchez Alvarado and Newmark 1998) and polychaetes (Paulus and Muller 2006).…”
Section: Wound Healing and Blastema Formationsupporting
confidence: 62%
“…3), triclads [18], rhabdocoels [19] and parasitic platyhelminths [20]. In contrast, proliferating cells in the epidermis occur in all other lophotrochozoans investigated, including annelids [21] (Fig. 4A–C), nemertines (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Complete regeneration from two segments is known in the oligochaete Enchytraeus japonensis and in the polychaete D. bermudensis , and our study showed a similar capacity in A. viride . Most individuals of A. viride could survive and regenerate from three segments, with the percentage of successful regenerates increasing with the number of regenerating segments (Paulus & Müller, ; Takeo, Yoshida‐Noro, & Tochinai, ). Comparative study of the regeneration of annelids might contribute to a better understanding of the evolutionary loss or gain of regenerative abilities.…”
Section: Discussionmentioning
confidence: 99%